Politik Hukum Penganggaran Dosen dalam Kerangka Hak Konstitusional atas Kebebasan Akademik - Rizki Mubarok (Equality : Jurnal Hukum dan Keadilan, 2026)
This study examines the political configuration of higher education budgeting in Indonesia and its implications for academic freedom. Despite the constitutional mandate allocating 20% of the national budget to education, the proportion specifically directed to higher education, particularly for improving lecturers’ welfare, has declined in recent years. Using a normative and comparative legal approach, this research analyzes how state budget policy reflects the principles of justice and the rule of law. The study employs Bertrand Russell’s theory of academic freedom, Friedrich Julius Stahl’s concept of the Rechtsstaat, and John Rawls’s theory of distributive justice as analytical frameworks. The findings indicate that the low level of lecturers’ welfare has weakened the material foundation of academic independence, leading to reduced intellectual autonomy in universities. Strengthening lecturers’ welfare through equitable budget distribution is therefore essential to realizing the constitutional ideal of a democratic and just legal state based on Pancasila.